PENGUATAN BUDAYA KERJA PENYULUH AGAMA NON-PNS DALAM PEMBINAAN UMAT HINDU DI KABUPATEN GIANYAR - I Nyoman Sueca (Guna Widya: Jurnal Pendidikan Hindu, 2018)
Increasing the resources and progress of the Hndu people in Gianyar district seems to require a process, the government’s efforts in improving human resources both in the area of development and religious education, all of which can not be separated from the readiness of leaders in an organization in providing services.In the management of the field of guidance of Hindus by non-civil servants, in order to create the strengthening of work culture, in the process of achieving progress, the increase of human resources in religion and religion, it is necessary commitment and efforts from extension workers to carry out their duties and obligations as public servants is a manifestation of clan karma.Efforts to improve the education of intlektual coaching-extension of Hindu entrepreneurs continue to be improved in order to educate and promote the Hindus in Gianyar regency. This is done in accordance with Law no. 20 of 2003, article 30, paragraph 2 states that religious education serves to prepare students to become members of the community who understand and practice the values of religious teachings. Strengthening the work culture of the counselor makes efficient effectiveness, what if the extension officer has performed performance sesuati with scheduled. Organizational culture in a government or private institution that is applied strongly and positively will make management efficient and effective, because it produces things like; values, behaviors, deliberations, and mission-oriented activities